Carry Trade Returns and Segmented Risk Pricing - Gordon Schulze (Atlantic Economic Journal, 2021)
The returns to carry trades are controversially discussed. There seems to be no unifying risk-based explanation of currency returns and stock returns, while the countries' interest rate differential plays a leading part in the carry-trade performance. Therefore, this paper addresses carry-trade returns from a risk-pricing perspective and examines if these returns can be connected to cross-country differences in risk pricing in the interest-rate market compared to the stock market. Data from Thomson Reuters Datastream and Federal Reserve Economic Data covering Australia, Japan, New Zealand, Switzerland and the United States were analyzed based on GMM estimation. The results indicate significant and persistent cross-country differences in risk aversion in the interest-rate market compared to the implied risk aversion in the stock market. This may offer opportunities for risk arbitrage and, therefore, a risk pricing-related explanation of carry-trade returns.
Keywords: E21; F31; G12; 330; Carry Trade; Currency Returns; Foreign Exchange; Risk Aversion; Stochastic Discount Factor